PREPARATION OF MULTIFUNCTIONAL LAYERED OXIDE REE-CONTAINING MATERIALS - Dryuchko, O. G.; Storozhenko, D. O.; Bunjakìna, N. V.; Ivanytska, I. O.; Khanyukov, V. O.; Kytayhora, К. O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The aim of this work was to study the processes of cooperative interactions among the structural components during the formation of the layered cation-structured perovskite-like oxide phases of rare earth and transition elements at the preparatory stages using the nitrates of elements with different electronic structure and thermal activation. Stages of such transformations and patterns of phase formation were established; factors of influence and their determinant ability were clarified; a number of physical and chemical properties of the formed intermediate phases (coordination of lanthanides nitrates) were studied.
Keywords: rare earth elements; alkaline metals; ammonium; alkaline earth metals; complex formation; water-salt systems; properties